(untitled) (Fiep Bulletin - online, 2011)
The objective of the present study was to identify the aspects ergonomic in drivers of bus of long distances, and its relation with the post of work. The date analysed were from the complaints relates to quality of life, the physical discomfort developed during the execution of the activities, and the habits of life related from the practice of physical activity. For the sample there were selected 80 drivers of bus of an enterprise of interstate bus of the south region of Brazil, in service of the profession. The instrument of collection of data was the questionnaire with referring questions the conditions of work, of health, habits and way of life when the practice of physical activity. The results were analysed using: descriptive statistic, descriptive, average, I divert standard and percentage. From the analysis significant percentages of physical discomfort happened in the spine were noted , principally in the lumbar region. The most reported complaints were: cramps, formications, numbness and located pains. The conclusion iis that the activity of the drivers of bus of long distances provokes different levels of srhinking muscle skinny-muscle, until producing physical significant discomforts that influence his quality of life and work. This is direct associate to the conditions of work, the pauses, the daily journey, the conditions of health, I as well as , the practice of physical activity.